Tuturan Makian dalam Film Serial Omar: Analisis Sosiolinguistik - Fathurrohim, Ilham Hanif; Nur, Tajudin; Nugraha, Tubagus Chaeru (Universitas Muhammadiyah Surakarta, 2024)
This research focuses on the analysis of swear words in the Omar Film Series, which is then linked to the social and cultural context of Arab society at that time. The Omar Series is a film that tells the story of the life of Umar Bin Khattab, the second caliph of Islam, from his youth until his death. This film, which consists of 30 episodes, is widely watched by students in Indonesia, both to study the history of the development of Islam and to learn Arabic. The research method used in this research is descriptive qualitative. To limit the research, researchers used Wijana and Rohmadi's theory which classifies swear words based on lingual units and their references, as well as theories regarding the function of swearing according to Andersson and Trudgill. The results show that the lingual units most often used in swear words in the film are in the form of clauses. Apart from that, the most common swearing references found in this film are curses, following the ancient Arabic culture of cursing. In addition, the most frequently found function is the abusive function, namely using swearing with the aim of insulting, degrading, or even cursing.